PIK3R2/Pik3r2 Activating Mutations Result in Brain Overgrowth and EEG Changes. Issue 6 (28th September 2020) - Shi, Xiuyu; Lim, Youngshin; Myers, Abigail K.; Stallings, Brenna L.; Mccoy, Almedia; Zeiger, Jordan; Scheck, Joshua; Cho, Ginam; Marsh, Eric D.; Mirzaa, Ghayda M.; Tao, Tao; Golden, Jeffrey A.
Abstract : Objective: Mutations in phosphatidylinositol‐4, 5‐bisphosphate 3‐kinase (PI3K) complex have been associated with a broad spectrum of brain and organ overgrowth syndromes. For example, mutations in phosphatidylinositol‐3‐kinase regulatory subunit 2 ( PIK3R2 ) have been identified in human patients with megalencephaly polymicrogyria polydactyly hydrocephalus (MPPH) syndrome, which includes brain overgrowth. To better understand the pathogenesis of PIK3R2 ‐related mutations, we have developed and characterized a murine model. Methods: We generated a knock‐in mouse model for the most common human PIK3R2 mutation, p.G373R (p.G367R in mice) using CRISPR/Cas9. The mouse phenotypes, including brain size, seizure activity, cortical lamination, cell proliferation/size/density, interneuron migration, and PI3K pathway activation, were analyzed using standard methodologies. For human patients with PIK3R2 mutations, clinical data (occipitofrontal circumference [OFC] and epilepsy) were retrospectively obtained from our clinical records (published / unpublished). Results: The PI3K‐AKT pathway was hyperactivated in these mice, confirming the p.G367R mutation is an activating mutation in vivo. Similar to human patients with PIK3R2 mutations, these mice have enlarged brains. We found cell size to be increased but not cell numbers. The embryonic brain showed mild defects in cortical lamination, although not observed in the mature brain. Furthermore, electroencephalogram (EEG) recordings from mutant mice showed background slowing and rare seizures, again similar to our observations in human patients. Interpretation: We have generated a PIK3R2 mouse model that exhibits megalencephaly and EEG changes, both of which overlap with human patients. Our data provide novel insight into the pathogenesis of the human disease caused by PIK3R2 p.G373R mutation. We anticipate this model will be valuable in testing therapeutic options for human patients with MPPH. ANN NEUROL 2020;88:1077–1094